Hamstring injury mechanisms and eccentric training-induced muscle adaptations: current insights and future directions - Andrews, M. H.; Shield, A. J.; Lichtwark, G. A.; Pincheira, P. A. (Sports Medicine, 2025)
Hamstring injuries are a major concern in sports owing to their high incidence and recurrence rates, highlighting the need for a deeper understanding of their mechanisms and prevention. This narrative review aims to inform hamstring injury prevention strategies by examining: (1) the causes of hamstring injuries, (2) the effectiveness of eccentric training in reducing injury risk, and (3) muscle adaptations from eccentric training that may offer protective effects. Hamstring injuries often occur during the late swing phase of running, potentially due to insufficient or delayed neural activation or an inability to generate the necessary force to decelerate the leg and resist active overstretching. In this phase, the hamstrings must produce large eccentric forces while operating at long lengths, placing them in a vulnerable position. Despite the potential of eccentric training to induce muscle adaptations that may reduce injury risk, current research has overly focused on architectural changes, particularly resting fascicle lengthening, without adequately exploring how these adaptations influence the functional behavior of hamstrings during exercise. In addition, the lack of research into adaptations of non-contractile and neural elements in the hamstrings following eccentric training represents a significant gap in the literature. This review argues for a broader focus on these underexplored areas to enhance hamstring injury prevention strategies. Further research is essential to fully understand the mechanisms behind muscle fascicle lengthening after eccentric training. Exploring functional and regional differences in hamstring adaptations and delving deeper into non-contractile and neural elements could enhance injury prevention strategies, potentially reducing the incidence of hamstring injuries.